Response of the Equilibrium Real Exchange Rate to Real Disturbances in Developing Countries - Khan, Mohsin (IMF Working Papers; Working Paper ;, 1991)
Using a simple dependent - economy framework, this paper outlines the links between the equilibrium real exchange rate and some of its fundamental exogenous determinants, mainly terms of trade movements and commercial policy changes. Drawing on existing studies of trade flows in developing countries, it is possible to derive plausible quantitative ranges for the response of the equilibrium real exchange rate to both external and policy-induced shocks. The results should be particularly relevant in designing real exchange rate targets and rules that allow for movements in the equilibrium real exchange rate in response to various shocks.